The Impact of Kindergarten Outdoor Policies and Physical Environments on Children’s Affordances to Play - Mariana Moreira; Rita Cordovil; Gueda Veiga; Frederico Lopes (Sakarya Üniversitesi Eğitim Fakültesi Dergisi)
The existence of specific quality indicators of kindergarten outdoor physical environments and pedagogical policies seems to promote different affordances to play, which impacts on children’s play behavior, and on their motor and socio-emotional (Berti, Cigala, & Sharmahd, 2019a, 2019b; Houser et al., 2019; Kyttä, 2004; G. T. Moore, Piwoni, & Kennedy, 2015) This article presents a methodology to be used in a PhD project, which aims to analyze the quality of the outdoor physical environments and pedagogical policies of 19 kindergartens in Gondomar (Portugal), to determine their impact on preschool children's play affordances. A comprehensive mixed methodology will be applied in two stages. At the first stage, an in-loco observation scale, and surveys completed by the kindergarten’s directors and educators will be used to assess the quality of outdoor physical environment and pedagogical policies. In the second stage, 2 kindergartens will be selected (one with high scores and one with low scores in the quality assessment). In each of them, the play yard choices, types of play and interaction with the peers will be analysed through RFDI sensors, participant and systematic observation, and video records. Children’s motor and socio-emotional competence will be assessed through standardized assessment batteries. Children’s perception about the kindergarten outdoor space will also be analyzed trough drawings and interviews. Surveys will be completed by educators and parents to assess their perceptions about outdoor play. This study aims to contribute to increase the scientific knowledge about the quality indicators regarding the outdoors physical environment and pedagogical practices of kindergartens, assessing their impact on children’s play behavior. This issue has particular importance after a long period of lockdown caused by the COVID-19 pandemic, in which outdoor play behaviors and movement were more restricted and have inevitably changed (Graber et al., 2020; S. A. Moore et al., 2020; Pombo, Luz, Rodrigues, & Cordovil, 2020).Keywords: Outdoor; Kindergarten; Policies; Physical Environment; Affordances; Children; Play